Arboe Rasmussen-sagen i årene 1916-20 - Hermansen, Karsten (Kirkehistoriske Samlinger, 1995)
The priest N.P.Arboe Rasmussen (AR)( 1866-1944) wrote in 1902 an article which was critical of the virgin birth. He had got his inspiration from the liberal theologian Harnack. 1910 AR delivered a lecture which started the debate concerning his continuance as a priest in the Danish national church. In 1913 AR applied for an office as a priest in Vålse in Lolland. The parishioners chose him, but the bishop, Wegener, refused to accept him. However, the social-liberal government wanted AR appointed, because this would state their tolerant church policy. As a countermove the bishops started legal proceedings against AR - as a criminal case. The Supreme Court acquitted, in 1916, AR but did not evaluate his suitability as a priest in the Danish national church. The political and religious left wing -and the government - understood this as an acceptance of AR in the church, while the right wing meant that nothing had been decided. The government tried in 1916 on the basis of the judgment to carry through a law which allowed priests in general to be directly subordinated the Minister of Ecclesiastical Affairs if the bishop refused to accept them. But the law did not pass. 1917 the Parliament adopted a special law which allowed AR to be priest without the acceptance of bishop Wegener. AR would come under the normal law as a priest when the 66 years old bishop Wegener retired in the near future. That is, if AR stayed in office for a longer time than Wegener then the tolerant church policy would be a formal reality! However, AR left Vålse in 1920, a disappointed man; Wegener was still in office. Therefore, the formal acknowledgement of the tolerant church policy had disappeared, and the government had lost in the political fight for a tolerant church. The political right wing had regained what had seemed to be lost with the special law in 1917. If the non-socialist parties had been in government in 1916 then AR had been removed already in 1916. This case was in other words rather political than religious. P.G.Lindhardt did in 1953 conclude that the possibility of a realization of the tolerant church already disappeared with the special law in 1917. Other historians which have worked with the case of Arboe Rasmussen have seen the case in a long perspective and therefore more or less ignored the conflict in the years 1916-20.